Form and meaning in cognitive morphology - Kardela, Henryk (Categories and Units in Language and Linguistics, 2020)
The paper applies Ronald Langacker’s conception of Baseline/Elaboration (B/Eorganisation)to derivative morphology. It is claimed that the B/E approach to linguisticstructure, according to which “structure and function are indissociable like the two sidesof a coin” (Langacker, 2016, p. 24), offers a viable, theoretically interesting account of thedynamic relationship between the form and meaning of morphological units.